2020
DOI: 10.1159/000506765
|View full text |Cite
|
Sign up to set email alerts
|

Colocalization of Tau but Not β-Amyloid with Cortical Superficial Siderosis in a Case with Probable CAA

Abstract: Cortical superficial siderosis (cSS) is a common feature in patients with cerebral amyloid angiopathy (CAA). The correlation between β-amyloid and/or tau pathology and the occurrence of cSS is unclear. We report on an 80-year-old male patient who was diagnosed with probable CAA according to modified Boston criteria and underwent longitudinal magnetic resonance imaging, amyloid positron emission tomography (PET), and additional tau PET imaging. Amyloid deposition presented predominantly in the contralateral hem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
1
4
1
Order By: Relevance
“…immediate vicinity to cSS deposition. This cohort-based finding confirmed the previous case report of one patient from this study (Brendel et al, 2020b).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…immediate vicinity to cSS deposition. This cohort-based finding confirmed the previous case report of one patient from this study (Brendel et al, 2020b).…”
Section: Discussionsupporting
confidence: 93%
“…In turn, this could facilitate improved judgment of Aβ-PET positivity by the specific analysis of cSS-positive brain regions. However, in a recent single-case analysis from our group (Brendel et al, 2020b), a patient with probable CAA did not show a regional increase of the Aβ-PET signal in brain areas affected by cSS. Thus, we aimed to explore this phenomenon in a larger cohort of ten patients with CAA who underwent GRE-T2 * -WI MRI and 18 F-florbetaben Aβ-PET.…”
Section: Introductioncontrasting
confidence: 61%
See 1 more Smart Citation
“…A previous case report demonstrated ipsilateral myelin loss and gliosis in the pyramidal tract lesion 5 years after a left middle cerebral artery infarction ( 45 ). As for the other tau PET tracers and CAA, two reports of Tau PET have been published ( 46 , 47 ). In the former report, paired helical filament (PHF) tau burden overlapped cerebral microbleeds and/or cSS on 18 F-AV1451 PET, raising the possibility that the characteristic markers of vascular amyloid were associated with local production of PHF tau ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the latter report, the amyloid deposition, evaluated by 18 F-florbetaben PET, was not different in vicinity of cSS, but tau depositions were elevated in vicinity of cSS-affected regions compared to non-cSS-affected brain regions. Their case of probable CAA suggested that cSS may be associated with an elevation in local tau accumulation but not with an increase in fibrillary amyloid deposition ( 47 ). 18 F-THK5351 PET has been reported to strongly bind to MAO-B derived from astrocytes and possibly tau, probably reflecting astrogliosis related CAA hematoma and cSS, also possibly tau accumulation in AD pathology ( 48 ).…”
Section: Discussionmentioning
confidence: 99%